Efektivitas Penerapan Model Webbed Learning terhadap Kemampuan Pemahaman Konsep Pembelajaran Tematik Peserta Didik Sekolah Dasar - Nabilah, Zahra Putri; Kowiyah, Kowiyah (Universitas Negeri Makassar, 2024)
This research aims to show how effective the use of the webbed learning model is on students' ability to understand thematic learning concepts in class IV elementary schools in East Jakarta. This research applies a quantitative experimental method by implementing a Post-Test Only Control Group Design. Data collection through tests and questionnaires. The data analysis obtained shows that the results of the t test using the independent test type are tcount 13.333 > ttable 2.001, so the conclusion that can be drawn is that H0 is rejected which states that H1 is accepted, there is the ability to understand thematic learning concepts of class IV elementary school students after implementing the webbed learning model. To strengthen the acquisition of research data, researchers distributed student response questionnaires with results of 85% qualifying as